O Instituto Histórico e Geográfico do Rio Grande do Sul e o espaço social dos intelectuais : trajetória institucional e estudo das redes de solidariedade (e conflitos) entre intelectuais (1920-1956) - Martins, Jefferson Teles (2015)
This thesis has the objective to analyze the trajectory of the Instituto Histórico e Geográfico do Rio Grande do Sul, since its foundation in 1920, going through the time when it was recognized as the legitimate producer of the historical knowledge in Rio Grande do Sul, until the time when that institution had its authority questioned. This analyzes has three main axes: first, it focus on the social space and objective conditions in which those intellectual agents moved and played on; second, it will be analyzed the process of mobilization as group in which those agents aimed to establish relations with the political field; third, the study also focus on the inner disputes amongst those agents who sought recognition and prestige as intellectuals in that institutional field. Besides that, in this analyzes the networks of those agents will receive special attention in order to understand their conflicts and disputes.